Pengaruh Ekstrak Etanol Daun Alpukat (Persea americana Mill.) terhadap Mortalitas Cacing Ascaris suum, Goeze in Vitro - Monica Citraningtyas Astarani; Bambang Sukilarso; Sri Haryati (Nexus Biomedika, 2013)
Background : Avocado leaves which have been known from phytochemical contain flavonoid, tannin katekat, quinone, saponin, and steroid/triterpenoid. Saponin and tannin are active substances which have anthelmintic effect. This research was to know the effect of avocado (Persea americana, Mill.) leaves ethanol extract toward the mortality of Ascaris suum, Goeze in vitro. Methods : This study was experimental laboratory research with the post test only controlled group design. The subjects were 150 adult Ascaris suum, Goeze, arranged into 6 groups. NaCl 0.9 % solution was treated to negative control group, while 5 mg/ml pirantel pamoat solution was treated to positive control. The others group were treated with 60%, 70%, 80%, 90% w/v of Avocado (Persea Americana, Mill.) leaves ethanol extract. Observation was done in every hour until all worm died. The data were analyzed by linear regression and probit analysis. Results : Probit analysis showed that LC50 and LT50 of Avocado leaves extract were 56.42% dan 665.15 minutes. Linear regression analysis showed there was significant (p < 0.05) effect between the time of death and variation of extract concentration. Conclusion : Avocado (Persea americana Mill.) leaves ethanol extract had significant effect toward the mortality of Ascaris suum, Goeze in vitro. Keywords : avocado leaves ethanol extract, Ascaris suum, LC50